Impact of Hypocaloric Diets on Weight Loss and Body Composition in Obese Dogs: A Meta-Analysis - Karoline Vanelli; Rafael Fernando Wisneski; Camila Estevão; Fernanda Caroline Mayer; Leandro Batista Costa; Saulo Henrique Webber; Cláudia Turra Pimpão (Animals, 2025)
Canine obesity is a complex, multifactorial condition marked by excessive body fat accumulation due to a sustained positive energy balance. Over the past decade, its global prevalence has risen significantly in most industrialized nations. Despite the availability of numerous commercial diets designed for obesity management in dogs, these products exhibit considerable variability in nutrient composition, and there is currently no standardized guideline on optimal macronutrient levels for effective weight loss. This study aimed to evaluate the effects of specific macronutrient levels on weight loss and body composition in obese dogs. A comprehensive literature search was conducted from 2022 to 2024 across PUBMED, Scielo, Web of Science, and Google Scholar. Out of an initial 1727 documents, 20 studies met the inclusion criteria and were incorporated into this meta-analysis. Diets with energy densities below 3.275 kcal, protein levels above 25%, total dietary fiber exceeding 12%, lower fat (<10%), and reduced non-nitrogenous extract (<40%) demonstrated beneficial effects on all evaluated parameters, including weight loss and body composition assessment. This meta-analysis provides evidence-based nutritional recommendations on optimal caloric, protein, fiber, fat, and carbohydrate levels for hypocaloric diet formulations, supporting healthy weight loss and lean mass preservation in obese dogs. These findings contribute to the development of effective dietary strategies that enhance canine quality of life and longevity.